MONUMENTS OF THE REPUBLIC OF LITHUANIA IN THE WORLD CULTURAL HERITAGE: INTERNATIONAL AND NATIONAL ASPECTS OF THEIR LEGAL STATUS - Martynenkа, I. E. (Teisė, 2015)
The article discusses the status of monuments inscribed on the List of World Cultural and Natural Heritage, UNESCO formed. The author analyzes the international conventions, national legislation and on this basis formulates a number of scientific and practical recommendations. Describing the World Heritage Site located in the territory of the Republic of Lithuania, proposals are being made to optimize the international legal documents and national legal acts.